Effect of citrus pectin on blood lipids and fecal steroid excretion in man - Kay, RM; Truswell, AS (The American journal of clinical nutrition, 1977)
Citrus pectin (15 g/day) was added for 3 weeks to metabolically controlled diets in nine subjects. Pectin was consumed with fruit and sugar as a gel in divided doses with meals. Plasma cholesterol concentrations were reduced by a mean of 13% (P < 0.001). Fecal fat excretion increased by 44% (P < 0.001); neutral steroids by 17% (P < 0.001) and fecal bile acids by 33% (P < 0.02). Plasma triglyceride levels did not change.